2014
DOI: 10.1111/ane.12293
|View full text |Cite
|
Sign up to set email alerts
|

Public stroke awareness and intent to call 112 in Sweden

Abstract: We confirm a rather low public awareness of stroke in Sweden, poorer among males and those with low education. With increasing age, a lower proportion indicated intent to call 112 for stroke symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 8 publications
6
36
0
Order By: Relevance
“…Analysis of data from the FAST-RIGHT study shows that 34.7% of the study participants in the 40-74 age group, and 36.6% in the 75-99 age group did not call EMS first [15], even though they had considered abnormal symptoms as "stroke onset." Similar to our results, 18.9% in Spain, [11] 28% in Sweden [22], 33.6% in America [9], and 35.5% in a small study in China [12] avoided calling an ambulance despite recognizing stroke onset. In clinical practice in China, this rate showed a significant increase to 82.1% [10].…”
Section: [Figure2 Position] Discussionsupporting
confidence: 90%
“…Analysis of data from the FAST-RIGHT study shows that 34.7% of the study participants in the 40-74 age group, and 36.6% in the 75-99 age group did not call EMS first [15], even though they had considered abnormal symptoms as "stroke onset." Similar to our results, 18.9% in Spain, [11] 28% in Sweden [22], 33.6% in America [9], and 35.5% in a small study in China [12] avoided calling an ambulance despite recognizing stroke onset. In clinical practice in China, this rate showed a significant increase to 82.1% [10].…”
Section: [Figure2 Position] Discussionsupporting
confidence: 90%
“…First, only stroke events leading to hospitalization or death outside hospital were captured. A recent study in Sweden showed that stroke awareness did not differ between patients with diabetes and individuals without regular healthcare contacts [24]. Therefore, we believe that the proportion of potential missed cases due to not seeking medical care should be the same between control subjects and individuals with diabetes.…”
Section: Discussionmentioning
confidence: 74%
“…The most commonly recognised risk factors for stroke across the studies were hypertension, high cholesterol, obesity and smoking (see Additional File 4). Out of eight studies (6,28,29,31,35,36,38,40) that asked open questions with regards to risk factors and gave a percentage of the number of people able to give at least one correct risk factor of stroke, the results ranged from 50.8% (31) to 89.5% (38). This means that in all of these eight studies, over half of participants were able to correctly identify a risk factor of stroke without being prompted.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Characteristics of included studies are displayed in Additional File 2. The 20 included studies (4)(5)(6)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) were all written between the years 2001 to 2015. Of the 20 studies, four (5,(27)(28)(29) were from Spain, two (30,31) were from Italy and two (32,33) from Croatia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%